COVID-19 in People with Diabetes: Perspectives from Saudi Arabia - Robert, Asirvatham A.; Al Dawish, Mohamed Abdulaziz (Current Diabetes Reviews, 2021)
Coronavirus disease 2019 (COVID-19) and diabetes have major impacts on the health of the population across the world. Since the beginning of the COVID-19 pandemic, people with diabetes have been identified to be more vulnerable to infection and at greater risk for hospitalization. As diabetes is one of the major health issues in Saudi Arabia, the current study describes the perspectives of COVID-19 in people with diabetes and the steps taken by the government to minimize its impact. Most patients with COVID-19 in Saudi Arabia experience mild illness, while people with diabetes are at increased risk of disease severity and mortality. The government of Saudi Arabia has taken several measures to control and mitigate the effect of the pandemic, as the Saudi population is gradually returning back to normal life. However, currently, there are limited studies from Saudi Arabia on COVID-19 among people with diabetes and the effectiveness of interventions. We emphasize the necessity for comprehensive research, which would provide a better understanding of the incidence of COVID-19 and its association with diabetes to develop evidence- based programs and policies in the country.
Keywords: COVID-19